Taxonomic studies on potter wasps (Hymenoptera: Vespidae: Eumeninae) of south India - Pannure, Arati; Belavadi, Vasuki V.; Carpenter, James M. (Zootaxa, 2016)
The family Vespidae is represented in India by four subfamilies: Vespinae, Polistinae, Stenogastrinae, and Eumeninae. The subfamily Eumeninae is the most species rich among the Vespidae. The potter wasps of south India are reviewed for the first time to comprise 31 valid genera. The genera Discoelius Latreille, 1809, Coeleumenes van der Vecht, 1963, Euodynerus Dalla torre, 1904, and Pseudonortonia Giordani Soika, 1936 are newly reported from south India. Diagnoses and a key to south Indian eumenine genera are given. A total of 72 species and subspecies are listed, 15 of them are newly reported from Karnataka and two species from Kerala.